The Effect of Panretinal Photocoagulation Treatment on Vision-Related Quality of Life of Patients with Proliferative Diabetic Retinopathy at Kariadi Hospital - Dea Prita Caesarita; Arief Wildan; Afrisal Hari Kurniawan; Andhika Guna Dharma (Majalah Oftalmologi Indonesia, 2022)
Objectives: Proliferative Diabetic Retinopathy (PDR) is one of the leading causes of blindness and visual loss. Panretinal Photocoagulation (PRP) reduces the risk of severe vision loss in PDR. Good visual acuity results can improve vision-related quality of life. The objective of this study is to evaluate the effect of laser PRP on patients with PDR on vision-related quality of life. Methods: In this prospective study, 30 PDR patients (12 men and 18 women) treated with PRP were included (mean age: 51 years, SD: 5,08 years). On average, patients received 1.264 laser spots. The National Eye Institute 7-Item Visual Function Index (VF-7) was used to evaluate patient's vision-related quality of life. The VF-7 was filled in by interview twice, at the beginning before laser PRP and at least 1 month after the completion of PRP. Comparison of VF-7 before and after laser PRP was performed. The correlation between alteration in visual acuity and VF-7 will be evaluated. Results: Mean VF-7 before laser PRP was 7.00 ± 0.00 and after laser PRP it was 3.43 ± 3.16 (p<0.001, Wilcoxon). VF-7 scores had a statistically significant difference between before and after laser PRP (p<0.05). There was a strong correlation between VF-7 score alteration with visual acuity (p <0.001, r 0.748). Conclusion: There was a significant improvement in vision-related quality of life following panretinal photocoagulation of patients with proliferative diabetic retinopathy.